L’imaginaire pictural de la matière photographique (1850–1860) : la cuisine de l’art, du peintre au photographe - Wicky, Érika (RACAR : Revue d'art canadienne / Canadian Art Review, 2015)
The writings on photography published in the 1850s reveal the emergence of a pictorial imaginary of photographic matter that grew in the margins of the amazement at a medium completely dominated by nature and the precise developments of the photographic technique. In some of these texts, photographers were likened to painters because of the application, in both techniques, of multiple layers of varied and more or less opaque substances. Inasmuch as it concerned the process of fabrication more than the image itself, the understanding of the work performed by photographers, of their action on matter, directly affected their social status. To reflect on the material imaginary of photography is then to interrogate the modalities of the joint emergence of the profession and of the figure of the photographer-artist at the very moment of the industrialization of photography.